Α‐Synuclein phase separation and amyloid aggregation are modulated by C‐terminal truncations. Issue 11 (6th May 2022) - Huang, Shuai; Mo, Xiaoli; Wang, Jieyi; Ye, Xinyi; Yu, Haijia; Liu, Yinghui
Abstract : The aggregation of α‐synuclein (α‐Syn) is a key pathological hallmark of Parkinson's disease (PD). α‐Syn undergoes liquid‐liquid phase separation (LLPS) to drive amyloid aggregation. How the LLPS of α‐Syn is regulated remains largely unknown. Here, we discovered that the C‐terminal region modulates α‐Syn phase separation through electrostatic interactions. The wild‐type (WT) and PD disease‐related truncated α‐Syn can co‐exist in the condensates. The truncated α‐Syn could dramatically promote WT α‐Syn phase separation. Further studies demonstrated that the truncated α‐Syn accelerated WT α‐Syn turning to amyloid aggregates by modulation of phase separation. Together, our findings disclose the role of the C‐terminal domain in the LLPS of α‐Syn and pave the path for understanding the mechanism of truncated α‐Syn in PD pathology. Abstract : α‐Synuclein (α‐Syn) undergoes liquid‐liquid phase separation (LLPS) to drive aggregation, but how this process is regulated remains unclear. We discovered that the C‐terminal region modulates α‐Syn LLPS through electrostatic interactions. The C‐terminal truncated α‐Syn dramatically promotes the phase separation and amyloid aggregation of wild‐type α‐Syn, suggesting a role for truncated α‐Syn in Parkinson's disease pathology.